A fuzzy C-means based algorithm for bias field estimation and segmentation of MR images - Bei Yan; Mei Xie; Jing-Jing Gao; Wei Zhao (2010 International Conference on Apperceiving Computing and Intelligence Analysis, 2010)
This paper proposes a novel algorithm for simultaneous estimation of the bias field and segmentation of tissues for magnetic resonance images. The algorithm formulated by modifying the objective function in the fuzzy C-means algorithm to include a bias field which is modeled as a linear combination of a set of basis functions. Bias field estimation and image segmentation are simultaneously achieved as the result of minimizing this modified fuzzy C-means objective function. The iterative algorithm for objective function minimization we provide converges to the optimal solution at a fast rate. The outstanding advantages of our method are that its result is independent from initialization, which allows robust and fully automated application and the superior performance compared with other methods. The proposed method has been successfully applied to 3-Tesla MR images and got desirable results.